BLACK TEA INFUSION AMELIORATES ENZYMATIC CHANGES INDUCED BY SUBCUTANEOUS EXPOSURE OF GASOLINE AND GM-10 IN MICE - Dave, Manjeet; Verma, Ramtej Jayram (International Journal of Research -GRANTHAALAYAH, 2015)
The present study was carried out to examine the ameliorative effect of black tea infusion on gasoline and GM-10 induced enzymatic changes in kidney of mice. Eighty healthy adult Swiss strain male albino mice weighing 32-35 gm were divided into eight groups including untreated control and various treated groups. Treated groups were subcutaneously administered with gasoline (412 mg/kg/day) and GM-10 low dose (206 mg/kg/day) and high dose (412 mg/kg/day) for 30 days. Black tea infusion (2%) was orally administered alone and along with gasoline and GM-10 through drinking water. All experimental animals were sacrificed on 31st day by cervical dislocation; kidney were isolated and used. Activities of succinic dehydrogenase, adenosine triphosphatase, acid phosphatase and alkaline phosphatase were assayed in kidney.The results revealed that subcutaneous administration of gasoline and GM-10 caused dose-dependent, significant enzymatic alterations in kidney of mice. Oral administration of black tea infusion along with subcutaneous treatment with gasoline and GM-10 significantly ameliorates all enzymatic changes induced by gasoline and GM-10 in kidney of mice.